An Approach of Tracking Control for Chaotic Systems - Jin Xing; Fangfang Zhang (Journal of Control Science and Engineering)
Combining the ergodicity of chaos and the Jacobian matrix, we design a general tracking controller for continuous and discrete chaotic systems. The control scheme has the ability to track a bounded reference signal. We prove its globally asymptotic stability and extend it to generalized projective synchronization. Numerical simulations verify the effectiveness of the proposed scheme.